Comparison of Intertypic Antigenicity of Aino Virus Isolates by Dot Immunobinding Assay Using Neutralizing Monoclonal Antibodies - Yoshida, Kazuo (American Society for Microbiology, 2000)
Neutralizing monoclonal antibodies (MAbs) against the Aino virus were prepared, and the neutralizing epitopes of the virus were defined by competitive binding assay. Seven continuous and overlapping neutralizing epitopes existed on the G1 glycoprotein of the Aino virus. Two antigenic domains were identified and were designated I and II, with domain II consisting of six epitopes. Dot immunobinding assays (DIAs) were performed with MAbs that recognized these seven neutralizing epitopes. DIAs were performed with 1 Australian strain and 21 isolates found in Japan between the years 1964 and 1995. The MAb response patterns of all isolates were divided into four groups. The Japanese isolates did not show large differences in antigenicity, but the antigenicity of the Australian strain collected in 1968 was significantly different from that of the Japanese strains; the Australian strain lacked reactivity to three epitopes and showed only low reactivity to one epitope.